The Application of the Principle of Balance Between the Parties in Standard Form Contracts under Civil Law - Suryaningsih Suryaningsih; Vivi Sylvia Purborini; Kasmin Kasmin; Rika Novitasari; Tikka Dessy Harsanti (Civiliza Publishing, 2026)
Standard form contracts are widely used in business activities due to their efficiency and practicality. However, their unilateral nature often places one party, particularly consumers, in a weaker bargaining position. This condition raises concerns regarding the application of the principle of balance between the parties as a fundamental principle in civil law. This study aims to analyze the application of the principle of balance in standard form contracts under civil law and to examine the extent to which existing legal regulations provide protection for the weaker party. This research employs a normative juridical method by analyzing statutory regulations, legal doctrines, and relevant legal principles, particularly those contained in the Civil Code and consumer protection laws. The results of the study indicate that although the principle of balance is recognized in civil law, its implementation in standard form contracts has not been fully realized, as many contractual clauses tend to favor business actors. Therefore, stronger legal safeguards and stricter supervision are required to ensure fairness and balance between the parties in standard form contracts.